Role of ABCC5 in cancer drug resistance and its potential as a therapeutic target - Pan, Yinlong; Wu, Mengmeng; Cai, Huazhong (Frontiers in Cell and Developmental Biology, 2024)
Over 90% of treatment failures in cancer therapy can be attributed to multidrug resistance (MDR), which can develop intracellularly or through various routes. Numerous pathways contribute to treatment resistance in cancer, but one of the most significant pathways is intracellular drug efflux and reduced drug concentrations within cells, which are controlled by overexpressed drug efflux pumps. As a member of the family of ABC transporter proteins, ABCC5 (ATP Binding Cassette Subfamily C Member 5) reduces the intracellular concentration of a drug and its subsequent effectiveness using an ATP-dependent method to pump the drug out of the cell. Numerous studies have demonstrated that ABCC5 is strongly linked to both poor prognosis and poor treatment response. In addition, elevated ABCC5 expression is noted in a wide variety of malignancies. Given that ABCC5 is regulated by several pathways in a broad range of cancer types, it is a prospective target for cancer treatment. This review examined the expression, structure, function, and role of ABCC5 in various cancer types.